Polymorphism of an Nα-Aroyl-N-Aryl-Phenylalanine Amide: An X-ray and Electron Diffraction Study - Lang, Markus; Goddard, Richard; Patzer, Michael; Ganapathy, Uday S.; Dick, Thomas; Richter, Adrian; Seidel, Rüdiger W. (MolBank, 2024)
In view of the rise of drug-resistant tuberculosis and difficult-to-treat related diseases caused by non-tuberculous mycobacteria, there is an urgent need for antimycobacterial drug discovery. Nα-aroyl-N-aryl-phenylalanine amides (AAPs) have been identified as antimycobacterial agents and are subject to lead optimization. The aim of the present study is to evaluate the impact of N-aryl ortho cyano substitution in a lead compound on the crystal and molecular structure and its in vitro activity against Mycobacterium abscessus. The title AAP can be conveniently synthesized from N-Boc-protected d-phenylalanine in two amide coupling steps using a previously established racemization-free method. Two polymorphic forms in the solid-state are described, as discovered by X-ray and electron diffraction. The introduction of a cyano group in the ortho position of the AAP N-aryl ring, however, leads to loss of in vitro activity against M. abscessus subsp. abscessus.